Effects of Nebivolol therapy on hemodynamic parameters and lipid profile compared to other beta blockers in patients with essential hypertension: a systematic review and meta-analysis - I Made Fermi Wikananda; I Gusti Ngurah Metta Nurcahya; Putu Gede Pradipta Mahardika Wijaya; I Gde Raka Widiana; Dwijo Anargha Sindhughosa (Babol University of Medical Sciences, 2024)
Background: Besides being commonly used to treat high blood pressure, beta blockers are a family of drugs that are primarily used to regulate irregular cardiac rhythms. Nebivolol is a third generation of beta blockers, which is highly cardioselective, about three times as selective as bisoprolol. In this study, we aimed to evaluate Nebivolol's effectiveness and safety in comparison to other beta blockers. Methods: We searched the online databases PubMed, ScienceDirect, and Cochrane Library for relevant RCTs evaluating Nebivolol's effect on hypertension management. Relative risk (WRR) and weighted mean difference (WMD), with a 95% confidence interval (CI) were utilized to quantify the impact of nebivolol medication in the treatment of hypertension using a random effects model. Results: Twelve RCTs are included in the study, the patient numbers in every attempt ranged from 42-273 and 1456 patients in all were included in this review. Nebivolol does not significantly reduce SBP, DBP and HR compared to other beta blockers (WMD −0.57 mmHg, 95% CI [−1.55;0.42 mmHg] p=0.12 ; WMD −0.27 mmHg, 95% CI [−1.36;0.82 mmHg] p=0.63 ; WMD 0.10 BPM, 95% CI [−4.11;1.31 BPM] p=0.96, respectively). Patients treated with Nebivolol has significantly lower LDL-C (WMD -8.88 mg/dL, 95% CI [−15.28; -2.48 mg/dL] p=0.007) and significantly higher HDL-C (WMD 2.30 mg/dL, 95% CI [0.75; 3.84 mg/dL] p=0.004. Conclusions: According to this study's findings, nebivolol is well tolerated and decreases LDL-C. And higher HDL-C than other beta blocker agents. This review does not recommend nebivolol as first-line treatment in hypertension as Nebivolol does not significantly reduce blood pressure and HR of patients.